Honorands and Slave-owners: Tracing the Fortunes of an Achaian Elite Family in IG IX 12 3, 721 - Hewitt, Matthew (Tekmeria, 2025)
This article is a study of a single block of marble from the West Lokrian polis of Chaleion, which hosts three separate inscriptions (IG IX 12 3, 721a-c): a dedication, a proxeny decree and a manumission by sale to Apollo. I first provide an overview of the history of the stone, as well as the dates, content and context of each inscription. I then propose that the homonymity between Kleogenes of Aigion, the recipient of proxenia in text b, and the Kleogenes who manumits his slave in text c suggests that they belonged to the same family. I explore the implications of this identification for tracing the fortunes of an elite Peloponnesian family in the wake of the disaster of 146. Furthermore, I argue that the act of freeing an enslaved person, along with its record, was employed by the second Kleogenes as a means of performing and establishing his own status. I suggest that this example is indicative of the fact that manumission inscriptions were firmly embedded within a culture of conspicuous elite display.